1998
DOI: 10.1136/thx.53.8.643
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of an auto-CPAP device for treatment of obstructive sleep apnoea

Abstract: Background-Auto-CPAP machines used in the treatment of obstructive sleep apnoea (OSA) are designed to vary the treatment pressure automatically in order always to apply the actually needed pressure. Consequently they should be able to achieve at least identical therapeutic effects as conventional constant pressure CPAP with a lower mean treatment pressure. The present study was designed to evaluate the therapeutic eYcacy and the treatment pressure of an auto-CPAP machine (REM+auto ® , SEFAM) in comparison with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0
6

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(51 citation statements)
references
References 21 publications
(11 reference statements)
3
41
0
6
Order By: Relevance
“…Starting from an initial 0.4 kPa (4 mbars), the pressure was increased in steps of 0.1 kPa (1 mbar) at intervals of o5 min when obstructive events (apnoeas, hypopnoeas or snoring) occurred. If no further events occurred during the next 30 min, the pressure was then reduced every 10 min in steps of 0.1 kPa (1 mbar) until they re-occurred, whereupon the pressure was increased once more in the manner described above [29]. On the second night of CPAP, the patients were treated with the minimum effective pressure established during the previous night.…”
Section: Continuous Positive Airways Pressure Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…Starting from an initial 0.4 kPa (4 mbars), the pressure was increased in steps of 0.1 kPa (1 mbar) at intervals of o5 min when obstructive events (apnoeas, hypopnoeas or snoring) occurred. If no further events occurred during the next 30 min, the pressure was then reduced every 10 min in steps of 0.1 kPa (1 mbar) until they re-occurred, whereupon the pressure was increased once more in the manner described above [29]. On the second night of CPAP, the patients were treated with the minimum effective pressure established during the previous night.…”
Section: Continuous Positive Airways Pressure Therapymentioning
confidence: 99%
“…Diagnostic polysomnographies were performed in the sleep laboratory by trained sleep laboratory technicians as described previously [29]. All variables were recorded on a computer (SleepLab, Jaeger and Toennies, Hoechburg, Germany), and included electroencephalography (C4/A1, C3/A2), bilateral electrooculography, submental electromyography, nasal airflow measured by oronasal thermistors, snoring detected by microphone, electrocardiography, thoracic and abdominal movements measured by uncalibrated inductive plethysmography, and oxyhaemoglobin saturation using a finger oxymeter (Microspan1 3040G; Jaeger and Toennies).…”
Section: Sleep Studiesmentioning
confidence: 99%
“…Some previous reports have indicated a preference towards APAP in treatment-naive patients [23,24], whereas others have reported no such preference [25,26]. However, the present study design was specifically chosen to directly compare these three APAP devices, an objective that would have been more difficult in treatment-naive patients.…”
Section: Discussionmentioning
confidence: 99%
“…In 12 studies (15)(16)(17)(18)(19)(20)(21)(22)(23)(26)(27)(28), there was no significant difference in AHI values, with scores for APAP being lower in four of the studies. In the other two studies (24,25), values for APAP were significantly higher than those for CPAP.…”
Section: Treatmentmentioning
confidence: 99%
“…In 12 studies (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)26,28), there was a comparison of treatment pressures. APAP treatment produced significantly lower pressures than CPAP treatment in nine of the studies (15)(16)(17)(18)(21)(22)(23)26,28), and there was no significant difference in two studies (20,24). The remaining study (19) reported the maximum rather than the mean pressure for APAP, which was higher than that obtained with manual titration.…”
Section: Treatmentmentioning
confidence: 99%